Advanced Cold Moderators : ACoM-6 - Conrad, Harald (Forschungszentrum Jülich Gmbh Zentralbibliothek, Verlag, 2004)
These are the Proceedings of the 6th Meeting of the International Collaboration on Advanced Cold Moderators. We apologize for the long delay in publishing these lecture notes, which is mainly the editor’s fault. On the other hand, despite the long time since our meeting, it was not possible to obtain all contributions to the Proceedings in full text version. Like in the editor’s case this is certainly due to the many other duties of our colleagues. In order to nevertheless present a complete account of the meeting we have included in an Appendix copies of what was collected from the authors during the meeting. The collaboration on Advanced Cold Moderators was initiated during a meeting at Forschungszentrum Jülich in July of 1997, when a small working group of experts from numerous institutions was established. After this inaugural meeting we had the second one, arranged by Renate Bercher and Günter Bauer of the Paul-Scherrer-Institut in Villigen (Switzerland) in February of 1998. The third meeting, ACoM-3, took place in Oak Ridge under the supervision of Trevor Lukas in June of the same year. The fourth meeting was organized by Heidrun Barnert-Wiemer of Forschungszentrum Jülich and held there in February of 1999. The fifth meeting took place in Berlin in connexion with a general workshop on moderator concepts for spallation sources organized by Thomas Gutberlet, then at the Hahn-Meitner-Institut in Berlin. Of the first three meetings only minutes were written up and supplemented with copies of a few presentations, which were available. The first “formal” proceedings were printed and distributed among the collaboration members and meeting participants for ACoM-4. Our sixth meeting, the proceedings of which we deliver here, was attended by thirtyfour colleagues from eight countries on three continents – a small but impressive assembly of experts in the field. They presented their latest results in theory, numerical computation and experiments on advanced cold moderator media like methane-hydrate, ...